CISPM-MS: A Tool to Predict Surface Subsidence and to Study Interactions Associated with Multi?Seam Mining Operations - Yi Luo (International Conference on Ground Control in Mining, 2012)
Multiple-seam mining operations induce surface subsidence basins different from those caused by mining in a single coal seam, and also disturb the mining operations in the other coal seams. A computer program, CISPM-MS (Comprehensive and Integrated Subsidence Prediction Model for Multiple Seam Mining), has been developed to predict the final surface movements and deformations as well as the interactions associated with multi-seam coal mining operations. The program applies a newly developed subsurface subsidence prediction model that is able to consider the geological stratification variations. In predicting surface subsidence, the surface movements and deformations caused by the individual mining operations as well as the interactive effects are all considered. A case study is conducted in this paper for validating the program.